2021
DOI: 10.1016/j.jamda.2020.11.027
|View full text |Cite
|
Sign up to set email alerts
|

Medications in Post-Acute and Long-Term Care: Challenges and Controversies

Abstract: Nursing Homes post-acute care long-term care medications prescribing deprescribing Pharmaceutical agents are a valuable resource to assist in the care of older persons. Their use in post-acute and long-term care settings is particularly notabledfor example, the proportion of nursing home residents taking 9 or more medications increased from 18% in the mid-1990s to 40% less than 15 years later. 1,2 Average drug counts are similarly high around the world, although there is considerable variation in use between s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 61 publications
0
3
0
Order By: Relevance
“…One of the main strengths of this study is that the topic of medication optimization in PA-LTC and how to address from an interdisciplinary perspective is under studied. 8 Despite the low survey response rate at 7.8%, we believe that these findings provide preliminary data for future research. It is important to note, that other web-based surveys of practitioners were also noted to range from 7% to 15% depending on whether incentives were given or not.…”
Section: Study Strengths and Limitationsmentioning
confidence: 78%
See 1 more Smart Citation
“…One of the main strengths of this study is that the topic of medication optimization in PA-LTC and how to address from an interdisciplinary perspective is under studied. 8 Despite the low survey response rate at 7.8%, we believe that these findings provide preliminary data for future research. It is important to note, that other web-based surveys of practitioners were also noted to range from 7% to 15% depending on whether incentives were given or not.…”
Section: Study Strengths and Limitationsmentioning
confidence: 78%
“…Additionally, there were multiple lessons learned from the rapid development as well as implementation of the MMG during the pandemic which can help to propel pragmatic clinical trials that will help us to reimagine medication management initiatives in PA-LTC. 8 For instance, comments suggested that this pandemic-centered MMG should be adapted into a post-pandemic guideline that can further tactics to address medication burden. For instance, aligning existing work such as advanced care planning focusing on resident-centered goals of care while discussing the continued needs of medications and potentially unnecessary monitoring (e.g., multiple finger sticks for serum glucose testing) helped to reduce the burden on the direct care staff and the residents.…”
Section: Discussionmentioning
confidence: 99%
“…Appropriate medication use is a challenge in all settings including the post-acute and long-term care sites; the proportion of nursing home residents taking nine or more medications has more than doubled in the past two decades, although prescribing trends differ based on locations. There is call for up-to-date lists, medication reconciliation, deprescribing, and keeping the regimen simple, while being cognizant of adverse drug effects (Sloane et al 2021).…”
Section: Periodic Medication Review and Reconciliationmentioning
confidence: 99%